Cutis verticis gyrata secondary to giant cerebriform intradermal nevus in a pediatric patient - Ilteris Oguz Topal; Ozgur Emek Kocaturk Goncu; Cem Leblebici; Sule Gungor; Hatice Duman; Aslı Vefa Erdemir (Wolters Kluwer Medknow Publications, 2017)
Cutis verticis gyrata (CVG) is a long-lasting and progressive condition in which there is hypertrophy and folding of the scalp skin. Cerebriform intradermal nevus (CIDN) is a rare cause of CVG. Here, we report a case with CIDN of the scalp in a 12-year-old girl. Dermatological examination showed a cerebriform appearance with accentuating folds and deep furrows, thickening in the temporal regions. We want to emphasize that CIDN should not be forgotten in the differential diagnosis of the causes of CVG.